Clientelism of the Idea of Young Voters in Creating Substantial Democracy in the 2024 General Election - Rahmaddian, Rahmaddian; Andika, Rio; Harahap, Muda H; Yusri, Arienaldi; M. Hafiz Al Habsy; Arizal, Arizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
As a tactical step away from the concept of democracy, general elections in Indonesia are always faced with the practice of political clientelism.These problems are certainly a warning of the death of substantial democracy. Amid these threats, the 2024 general election has a different vote map from previous periods, where the proportion of young voters exceeds 50% of the national vote. This study aims to see the potential role that young voters can play in the 2024 general election to create substantial democracy. This article is a literature study through collecting library data, reading, recording, and processing research materials. In general, this article finds that young voters have a fairly high level of concern for environmental and climate issues after the issue of corruption. In particular, this article shows that climate and environmental issues can become a political narrative that encourages the creation of substantial democracy in the 2024 general election. In the pattern of political clientelism, the 2024 general election can form substantial democracy through the propositions of young voters and their interests, which will form a political narrative based on ideas.